Characterization of physicochemical qualities and starch structures of two indica rice varieties tolerant to high temperature during grain filling. (May 2020) - Fan, Xiaolei; Li, Yingqiu; Zhu, Yun; Wang, Jingdong; Zhao, Jie; Sun, Xiaosong; Pan, Yuntao; Bian, Xinyue; Zhang, Changquan; Zhao, Dongsheng; Liu, Qiaoquan
Abstract: An extreme high temperature during grain filling is an important environmental factor that reduce the yield and quality of rice. In this study, we compared the grain appearance, composition and starch structure of four rice varieties response to high temperature during grain filling. The results obviously revealed that two indica AUS varieties Halwa and Jamir showed more tolerance to high temperature during grain filling than either the japonica Nipponbare or another AUS rice DJ24. The data showed that Halwa and Jamir presented less chalkiness, less grain weight loss, less change of endosperm components as well as starch structure than Nipponbare and DJ24 under high temperature treatment. Hence, the results implied that Halwa and Jamir might be useful targets to further identify genetic mechanism response to high temperature, at least during grain filling and endosperm development. Moreover, these AUS varieties have potential application value in further breeding of rice with good quality and heat tolerance. Graphical abstract: Image 1 Highlights: Jamir and Halwa are two AUS rice varieties that originated from low latitudes. The yield and quality characteristics of Jamir and Halwa were hardly affected by high temperature. The influences of high temperature on the starch fine structure of Jamir and Halwa were much slighter.